Plant selection and avoidance by the Bornean elephant (Elephas maximus borneensis) in tropical forest: does plant recovery rate after herbivory influence food choices?. (24th April 2014) - English, Megan; Gillespie, Graeme; Ancrenaz, Marc; Ismail, Sulaiman; Goossens, Benoit; Nathan, Sen; Linklater, Wayne
Abstract: The plant vigour hypothesis proposes that herbivores should favour feeding on more vigorously growing plants or plant modules. Similarly, we would expect herbivores to favour plants that regrow vigorously after herbivory. Larger animals, like elephants, may also select plant species relative to their availability and prefer species with larger growth forms in order to meet their intake requirements. The food preferences of the Bornean elephant ( Elephas maximus borneensis ) in the Lower Kinabatangan Wildlife Sanctuary, Sabah, Malaysia, were investigated along 12 transects in areas where elephants were recently sighted feeding. One hundred and eighty-two plants were eaten and 185 plants were measured for species availability along transects. Species vigour was determined by the monthly regrowth in new shoot length after elephant feeding and the number of new shoots produced on each plant. Measurements were carried out on each plant for 9 mo or until the new shoot was eaten. Plant sizes were determined from their basal diameter. The Bornean elephant did not prefer more vigorous species or species with larger growth forms. New shoots did not grow longer on preferred than avoided species. Additionally, unlike other elephants that live in a forest environment, the Bornean elephant preferred species from the Poaceae (specifically Phragmites karka and Dinochloa scabrida ) over other plant types including gingers, palms, lianas and woody trees.